2009
DOI: 10.1007/s00228-009-0737-1
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and pharmacodynamics of prasugrel in healthy Chinese, Japanese, and Korean subjects compared with healthy Caucasian subjects

Abstract: Mean exposure to the prasugrel active metabolite following prasugrel 60-mg LD and during daily 10-mg or 5-mg MD was higher in each of the Asian groups than in the Caucasian group, which resulted in greater platelet inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 11 publications
2
58
1
Order By: Relevance
“…It was reported that in healthy European subjects, prasugrel at a dose of 60 mg showed about 80% platelet aggregation inhibition, which was almost the same as that in Japanese subjects receiving 20 mg prasugrel 19. This might be related to the plasma concentration of the active metabolite of prasugrel in Asian groups being found to be higher than that in white groups 20. The lower mean body weight of Asian subjects compared with white subjects may contribute to the higher concentration of the active metabolite in Asians.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that in healthy European subjects, prasugrel at a dose of 60 mg showed about 80% platelet aggregation inhibition, which was almost the same as that in Japanese subjects receiving 20 mg prasugrel 19. This might be related to the plasma concentration of the active metabolite of prasugrel in Asian groups being found to be higher than that in white groups 20. The lower mean body weight of Asian subjects compared with white subjects may contribute to the higher concentration of the active metabolite in Asians.…”
Section: Discussionmentioning
confidence: 91%
“…Studies on healthy Caucasian and Chinese subjects suggested that Pras-AM exposure was higher in Chinese subjects than that in Caucasians [5] ; the study in Chinese, Korean, and Japanese populations also showed higher exposure to Pras-AM and higher degree of platelet inhibition in these groups than in Caucasian populations [6] .…”
Section: Acta Pharmacologica Sinica Npgmentioning
confidence: 87%
“…The LD (dose received on d 1) was 60, 30, or 30 mg, and the MD (dose received once daily on d 2 through 11) was 10, 7.5, or 5 mg. The dosing regimens were based on other trials that identified higher overall exposure and an elevated overall PD response in Asian versus Caucasian subjects in addition to subgroup analyses by ethnicity, body weight, and age [5][6][7] . The drug was supplied as a tablet containing 5, 7.5, or 10 mg of prasugrel as a hydrochloride salt.…”
Section: Subjectsmentioning
confidence: 99%
“…[36][37][38][39][40][41][42] In a single-centre study of healthy volunteers, the level of inhibition of platelet aggregation induced by 20 μmol/l ADP in East Asian individuals taking 5 mg of prasugrel daily did not differ from that in white individuals taking 10 mg of p rasugrel daily (mean value at 4 h last-dose: 68.9% vs 70.1%). 40 In Japanese patients undergoing PCI, 15 mg loading and 3.75 mg maintenance doses of prasugrel achieved a faster, higher, and more-consistent antiplatelet effect than 300 mg loading and 75 mg maintenance doses of clopidogrel. 41 Likewise, the exposure of ticagrelor and its major active metabolite (AR-C124910XX) was higher in East Asian individuals than in white individuals after loading and maintenance doses.…”
Section: P2y 12 Inhibitors In East Asian Patientsmentioning
confidence: 88%
“…In individual studies, the level of the prasugrel active metabolite was 30-47% higher in East Asian patients than in white patients after loading and maintenance doses. [36][37][38][39][40] After adjusting for body mass, active metabolite exposure was still 19% higher in East Asian patients than in white patients, 40 and this finding was more prominent (45-56% higher) in patients with a low body mass (<60 kg). 38 The higher exposure of the prasugrel active metabolite in East Asian individuals than in white patients translates into the pharmacodynamic profile.…”
Section: P2y 12 Inhibitors In East Asian Patientsmentioning
confidence: 98%